Visualization of Sex Identification in Red‐Crowned Crane (Grus japonensis) via Recombinase‐Aided Amplification Combined With Pyrococcus furiosus Argonaute Assay - Shenluan Tan; Tongtong Zhan; Fanwen Zeng; Xuanjiao Chen; Tanzipeng Chen; Li Li; Hengxi Wei; Shouquan Zhang; Kejing Zuo (Ecology and Evolution)
ABSTRACT The red‐crowned crane (Grus japonensis), a Class I protected animal in China, inhabits Northeast Asia, including China, Russia, and Japan. As sex‐monomorphic birds, red‐crowned cranes cannot be directly distinguished between females and males through observation. Molecular methods are accurate and stable for sex identification in birds and are widely used in zoos and farms. With the development of isothermal techniques, recombinase‐aided amplification (RAA) has provided novel insights into bird sexing owing to its low equipment dependence and rapid amplification. Advancements in the Pyrococcus furiosus Argonaute (PfAgo) biosensor have facilitated clinical detection. In this study, an innovative sex identification system was developed by integrating RAA and PfAgo in red‐crowned cranes. The RAA‐PfAgo system identified both females and males with remarkable accuracy. Via proper design of primers set, gDNA and probe, the RAA‐PfAgo system can complete visual detection, with detection limits between 0.35 ng/μL and 0.035 ng/μL under optimal conditions. The test samples exhibited strong green fluorescence in females, whereas no fluorescence was observed in males under blue light. The results of RAA‐PfAgo in the field were consistent with those obtained using conventional PCR. This study provides a high degree of rapidity, accuracy, and sensitivity for the sex identification of red‐crowned cranes.